Synthesis, Characterization, And Photoluminescence Properties Of Ester Oligomers Containing Fluorene, Fluorescein And Curcumin Respectively For Potential Chemosensor Application - Ong, Hoay Ching (2021)
Three new homologous series of new ester oligomers containing fluorene (PF), fluorescein (FL) and curcumin (CM) on the backbone, respectively had been successfully synthesized and characterized. The molecular structures of the synthesized monomers and ester oligomers were elucidated by CHN, ATR-FTIR and FT-NMR (1D and 2D NMR). The synthesized ester oligomers showed high solubility in most of the common organic solvents, such as chloroform, tetrahydrofuran and acetone.